Macroeconomic structural change likely increases inequality in India more than climate policy - Marian Leimbach; Michael Hübler; Hendrik Mahlkow; Lorenzo Montrone; Eduard Bukin; Gabriel Felbermayr; Matthias Kalkuhl; Johannes Koch; Marcos Marcolino; Frank Pothen; Jan Christoph Steckel (Environmental Research Letters, 2024)
The decarbonization of India's economy will have different effects across income groups. As India is in the middle of the transformation process from an agriculture-based economy towards an industry- and service-based economy, called economic structural change, the extent of income distribution across households strongly depends also on the speed of economic transformation. While a number of recent studies have analyzed the distributional effects of carbon pricing, the specific role of structural change across sectors has not been in the focus of the related literature. Our study contrasts distributional effects from climate policy with distributional effects from structural change in India and asks how far carbon pricing supports or hinders structural change and development. We develop and apply a comprehensive model framework that combines economic growth and international trade dynamics related to structural change with detailed household income and expenditure data for India. Our study shows that changes in income and inequality due to carbon pricing vary with changes in the sectoral structure of an economy. Our results indicate that carbon pricing tends to delay economic structural change by retarding the reallocation of economic activities from the agricultural sector to the manufacturing sector. Furthermore, the results emphasize that the increase in inequality due to structural change is substantially stronger than due to carbon pricing. Consequently, socially sensitive policies supporting the process of structural transformation appear to be more important for poor households than lowering climate policy ambitions.
Keywords: Q54; O11; Q56; 330; Structural Change; Climate Policy